The title in research: short or long? - Luis Alberto Corona Martínez; Mercedes Fonseca Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
The title of a scientific article, a research project or the thesis final report is intended to provide guiding information about the content of the study. Based on the research problem-objective-title relationship, an analysis is made of one of the title´s most marked qualities: its extension. Derived from this analysis, it is concluded that in assessing the title of a research work´s quality, the priority, what is truly relevant is its precision and not its extension.